Pengaruh Literasi Keuangan dan Persepsi Risiko terhadap Minat Investasi Mahasiswa di Pasar Modal dengan Ekspektasi Return sebagai Variabel Mediasi : Studi Empiris pada Mahasiswa Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur, Jakarta, 2026 - Nila Nur Rafiah Syahni; Yuphi Handoko Suparmoko (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to conduct an in-depth analysis of the influence of financial literacy and risk perception on college students’ interest in investing in the capital market, with expected Return as the mediating variable. This study employs a quantitative research method. The population for this study consists of 1.620 students from the Faculty of Economics and Business at Universitas Budi Luhur. Based on calculations using the Slovin formula, a representative sample of 321 respondents was selected using purposive sampling, with the criterion that all respondents had real-world experience and active investment accounts in the capital market. The data analysis technique used was Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results of the study indicate that: Financial Literacy has a positive and significant effect on students’ Investment Interest; Risk Perception has a positive and significant effect on students’ Investment Interest; Financial Literacy has a positive and significant effect on Return Expectations; Risk Perception has a positive and significant effect on Return Expectations; Return Expectations have a positive and significant effect on students’ Investment Interest; and Return Expectations were empirically proven to partially (partial mediation) and significantly mediate the effects of Financial Literacy and Risk Perception on Investment Interest. The implications of this study confirm that a combination of rational financial understanding and the courage to manage risk, coupled with realistic Return expectations, serves as the primary driver of actual investment activity among college students.